2006
DOI: 10.1038/sj.onc.1209829
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenol EGCG suppresses cigarette smoke condensate-induced NF-κB activation in normal human bronchial epithelial cells

Abstract: Cigarette smoke is a powerful inducer of inflammatory responses resulting in disruption of major cellular pathways with transcriptional and genomic alterations driving the cells towards carcinogenesis. Cell culture and animal model studies indicate that (À)-epigallocatechin-3-gallate (EGCG), the major polyphenol present in green tea, possesses potent anti-inflammatory and antiproliferative activity capable of selectively inhibiting cell growth and inducing apoptosis in cancer cells without adversely affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 36 publications
4
66
0
4
Order By: Relevance
“…60,61 Therefore, increased RelA/p65 expression is possibly because of increased phosphorylation of RelA/p65 on ser276 as our results show. Consistent with in vitro studies, 62 CS exposure also induced the phosphorylation of RelA/p65 on ser536 in the lungs. Furthermore, the basal level of phosphorylation of RelA/p65 on ser536 was also increased in phoxϪ/Ϫ and gp91 phoxϪ/Ϫ mice compared to the airexposed control WT mice.…”
Section: Discussionsupporting
confidence: 73%
“…60,61 Therefore, increased RelA/p65 expression is possibly because of increased phosphorylation of RelA/p65 on ser276 as our results show. Consistent with in vitro studies, 62 CS exposure also induced the phosphorylation of RelA/p65 on ser536 in the lungs. Furthermore, the basal level of phosphorylation of RelA/p65 on ser536 was also increased in phoxϪ/Ϫ and gp91 phoxϪ/Ϫ mice compared to the airexposed control WT mice.…”
Section: Discussionsupporting
confidence: 73%
“…In neuronal cells, EGCG has been suggested to induce PKC activity, resulting in neuroprotection (Mandel and Youdin, 2004). Also, NF-κB inhibition has been shown to suppress oxidative stress-induced epithelial cell cytotoxicity/death (Jin et al, 2007;Syed et al, 2007). We speculate that similar signaling mechanisms mediate PP-60, ECG and EGCG bladder cytoprotection, and further studies are underway to probe changes in gene expression with catechin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] Those studies showed that chemoprevention agents including grape seed proanthocyanidins, epigallocatechin-3-gallate, and resveratrol repressed UVB-induced nuclear NF-B activity and cytosol IKK␣ levels in the mouse skin or keratinocytes, [46][47][48] suggesting that elevated IKK␣ levels may contribute to activation of NF-B after treatment with UVB. However, in the current study, we showed that NF-B activity was higher in Ikk␣ ϩ/Ϫ than in wild-type keratinocytes and that reduction in IKK␣ expression promoted UVB-induced skin carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%